2021
DOI: 10.1016/j.isci.2020.101892
|View full text |Cite
|
Sign up to set email alerts
|

NADPH performs mediated electron transfer in cyanobacterial-driven bio-photoelectrochemical cells

Abstract: Summary Previous studies have shown that live cyanobacteria can produce photocurrent in bio-photoelectrochemical cells (BPECs) that can be exploited for clean renewable energy production. Electron transfer from cyanobacteria to the electrochemical cell was proposed to be facilitated by small molecule(s) mediator(s) whose identity (or identities) remain unknown. Here, we elucidate the mechanism of electron transfer in the BPEC by identifying the major electron mediator as NADPH in three cyanobacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
145
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(164 citation statements)
references
References 99 publications
15
145
1
Order By: Relevance
“…We have recently reported that under illumination, NADPH is the major endogenous mediator which transfer electrons between cyanobacterial cells and the anode (40). There, 2Dfluorescence maps (2D-FM) measured the accumulation of NAD(P)H in the external cellular media (ECM).…”
Section: Endogenous and Exogenous Mediators Can Perform Mediated Electron Transfer Betweenmentioning
confidence: 99%
See 2 more Smart Citations
“…We have recently reported that under illumination, NADPH is the major endogenous mediator which transfer electrons between cyanobacterial cells and the anode (40). There, 2Dfluorescence maps (2D-FM) measured the accumulation of NAD(P)H in the external cellular media (ECM).…”
Section: Endogenous and Exogenous Mediators Can Perform Mediated Electron Transfer Betweenmentioning
confidence: 99%
“…Higher photocurrents of up to 500 µA/cm 2 were obtained by utilization of isolated thylakoid membranes from spinach with the addition ferricyanide ions (FeCN) for MET. In most cases, addition of the PSII inhibitor 3-(3,4-dichlorophenyl)-1,1-dimethylurea (DCMU) to photosynthetic organisms or isolated membranes inhibits harvested photocurrent, indicating that the major electron source is PSII (30,38,39) However, in some cases electrons from the respiratory system can be collected by the photosynthetic membrane, bypassing PSII (37,38,40). As isolated membranes are disconnected from photodamage cellular repair mechanisms, a decrease in current levels is apparent after 10 minutes of illumination (30).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Saper et al 28 reported that Synechocystis could secrete some undefined small molecules to shuttle electrons to the anode. Similarly, Shlosberg et al 29 showed that Synechocystis employed endogenous NADPH as an electron mediator to generate bioelectricity in bio-photoelectrochemical cells.…”
Section: Resultsmentioning
confidence: 98%
“…Moreover, they are easy to culture, amenable to genetic manipulation 8 , grow fast, and possess a simple cell structure compared with eukaryotes. Many studies on the mechanism of EET have been conducted using cyanobacteria [9][10][11][12][13][14][15] , and so far, direct EET via conductive nanowires 16 and indirect, mediated EET by endogenous mediators 14,15,17 have been put forward as possible EET pathways; some suggest that the latter is more likely than the former to occur in the case of cyanobacteria 2,18 .…”
Section: Introductionmentioning
confidence: 99%